1999
DOI: 10.1103/physreve.60.2193
|View full text |Cite|
|
Sign up to set email alerts
|

Partially ionized hydrogen plasma in strong magnetic fields

Abstract: We study the thermodynamic properties of a partially ionized hydrogen plasma in strong magnetic fields, B ∼ 10 12 − 10 13 G, typical of neutron stars. The properties of the plasma depend significantly on the quantum-mechanical sizes and binding energies of the atoms, which are strongly modified by thermal motion across the field. We use new fitting formulas for the atomic binding energies and sizes, based on accurate numerical calculations and valid for any state of motion of the atom. In particular, we take i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 69 publications
0
113
0
Order By: Relevance
“…Castellani & Degl'Innocenti (1999) noticed that the adoption of the Itoh et al (1983) evaluations, present in the STEV database, instead of the Hubbard & Lampe (1969) ones, adopted by the Dartmouth database, leads to an increase of the helium core of about 0.005 M and thus to a corresponding (1983) and Hubbard & Lampe (1969) ones, but closer to the Itoh et al (1983) results. In Cassisi et al (2007) the opacity calculations by Potekhin (1999) and Potekhin et al (1999) were improved by including the electron-electron scattering in partially degenerate and non degenerate matter. The authors found that the change of the conduction treatment from Potekhin et al (1999) to Cassisi et al (2007) leads to a reduction of M He c by about 0.006 M with a corresponding decrease of TRGB luminosity of Δ log L/L ≈ 0.03 and of the ZAHB luminosity by Δ log L/L ≈ 0.02.…”
Section: Comparison With Recent Stellar Model Databasesmentioning
confidence: 99%
“…Castellani & Degl'Innocenti (1999) noticed that the adoption of the Itoh et al (1983) evaluations, present in the STEV database, instead of the Hubbard & Lampe (1969) ones, adopted by the Dartmouth database, leads to an increase of the helium core of about 0.005 M and thus to a corresponding (1983) and Hubbard & Lampe (1969) ones, but closer to the Itoh et al (1983) results. In Cassisi et al (2007) the opacity calculations by Potekhin (1999) and Potekhin et al (1999) were improved by including the electron-electron scattering in partially degenerate and non degenerate matter. The authors found that the change of the conduction treatment from Potekhin et al (1999) to Cassisi et al (2007) leads to a reduction of M He c by about 0.006 M with a corresponding decrease of TRGB luminosity of Δ log L/L ≈ 0.03 and of the ZAHB luminosity by Δ log L/L ≈ 0.02.…”
Section: Comparison With Recent Stellar Model Databasesmentioning
confidence: 99%
“…In strong magnetic fields, however, the binding energies of atoms increase (for a review, Lai 2001; Potekhin, these proceedings; see also Fig. 7), and for temperatures and fields appropriate for INS, a fraction of up to 10% of neutral hydrogen will be present (Potekhin et al 1999). From initial model-atmosphere calculations that take the presence of neutral hydrogen into account , see their Fig.…”
Section: Hydrogenmentioning
confidence: 99%
“…near P ? (see Potekhin et al 1999), and we have used the fact that the oscillator strength is nonzero only when P ¼ P 0 (in the dipole approximation). The CM coupling effect will significantly smooth out the divergent behavior at !…”
Section: Analytic Model Of the Polarization Of Atomic Gas: Effect Of mentioning
confidence: 99%
“…In addition, because of the relatively high atmosphere density, a proper treatment should take account of the plasma nonideality that leads to Stark broadening and pressure ionization. Recently, thermodynamically consistent equations of state (EOSs) and opacities have been obtained for a magnetized, partially ionized H plasma for 8 ; 10 11 G P B 10 15 G (Potekhin et al 1999;, 2004. These EOSs and opacities have been implemented by for modeling NS atmospheres.…”
Section: Introductionmentioning
confidence: 99%